A novel anticoagulant peptide from the Nori hydrolysate. (January 2016) - Indumathi, P.; Mehta, Alka
Highlights: First report of an anticoagulant peptide from the Nori. Sequence of peptide is NMEKGSSSVVSSRM (+15.99) KQ, molecular mass of 1.77 KDa. Anticoagulation activity was measured by microtiter plate reader. The peptide is non-cytotoxic and has similar order of activity as that of heparin. Abstract: A potent and novel anticoagulant peptide was enzymatically isolated from the edible seaweed Porphyra yezoensis (commercially known as Nori). The pepsin hydrolysate showed 35% degree of hydrolysis and exhibited higher anticoagulant activity than undigested crude. The hydrolysate was fractionated by 4 sequential steps using size exclusion on Sephadex G-100, anion exchange, Sephadex G25 chromatography and desalting by Sephadex G-10. The purified peptide showed a single peak on RP-HPLC. The molecular mass of the peptide obtained by MS/MS analysis was 1.77 kDa and its sequence was identified as NMEKGSSSVVSSRM(+15.99)KQ. In vitro anticoagulation assays of purified peptide for clotting time with human plasma showed a dose-dependent prolongation of activated partial thromboplastin time from normal 35 s to 320 s with IC50 value of 0.3 µM. It did not prolong prothrombin or thrombin time. These results emphasise that the peptide interacts with the clotting factors involved in the intrinsic pathway of coagulation.